An Assessment of Sustainability Disclosures in Oil and Gas Listed Companies in Nigeria - Nwobu, Obiamaka Adaeze; Ngwakwe, Collins; Owolabi, Akintola; Adeyemo, Kingsley (International Journal of Energy Economics and Policy, 2021)
This paper assesses the level of corporate sustainability disclosures in an environmentally-sensitive industry in Nigeria - the oil and gas industry. The paper aims to evaluate the extent of sustainability disclosure in the annual report’s oil and gas industries. The study retrieves secondary data on sustainability disclosure for 10 years (2010 - 2019) from eight oil and gas industries listed in the Nigerian stock exchange through a desktop approach and content analysis methodology. Content analysis of the sustainability disclosure is to identify items of sustainability disclosed in the annual reports. The paper assesses the extent of disclosure by adopting the global reporting initiative’s scoring index. Findings from the analysis indicate a very low-level climate change and environmental pollution disclosure. Only 13.8% of the companies disclosed their impact on climate change and environmental pollution. On the contrary, all the companies revealed their community investment, which this paper regards as legitimizing smokescreen ecological pollution. The paper contributes to the literature by connecting the legitimacy theory to the decoying sustainability disclosure of oil and gas companies in Nigeria. In conclusion, the study recommends more stringent sustainability disclosure policies for the oil and gas to provide more information for environmental and climate change advocates and investors in censuring the companies, which might instill improved environmental compliance. Keywords: Climate Change, Greenhouse Gas Emissions, Governance Indicators, Oil and Gas, Renewable Materials, Social Indicators, Sustainability Disclosures JEL Classifications: M4, M14, M140, Q53, Q54, Q56, Q57 DOI: https://doi.org/10.32479/ijeep.11095